Klub Alumni Pravne fakultete - Koritnik, Boštjan (Pravnik, 2023)
In late March 2023, the University of Ljubljana Faculty of Law Alumni Club conducted its annual general assembly at the Faculty’s premises, utilising both in-person attendance and audio-video conferencing. The president of the association is academician Janez Kranjc. Goals and tasks of the association are building social links among graduates of the Faculty of Law of the University of Ljubljana among themselves and with the faculty and its teachers and colleagues; professional and scientific cooperation of graduates of the Faculty of Law with the Faculty; care for the reputation of the legal profession and education provided by the Faculty of Law, strengthening social ties between the Faculty of Law and its graduates; promotion of legal knowledge in the social environment of the association; contributing to the support of the activities of the Faculty of Law and its students. The reports for 2022 and the work plan for 2023 were approved by the general assembly.
Keywords: alumni; načrt dela; ocene in poročila; Pravna fakulteta Univerze v Ljubljani; slovenska društva